Model Transformasi Pendidikan Pesantren: Studi Kasus Di Pp. Darul Dakwah Mojokerto - Achmad Zainul Mustofa Al Amin (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
Pesantren is the oldest educational institution in the course of Indonesian life since hundreds of years ago. Pesantrens are required to re-understand their identity as Islamic educational institutions, while on the other hand, pesantren are also faced with demands to open up to several modern education systems originating from outside the pesantren. In this case, Islamic boarding schools are faced with demands to contribute to improving the quality of education, the quality of human resources needed in modern life. The aims of this research are: (1) to describe the transformation model of Islamic boarding school education in Darul Dakwah Sooko Mojokerto Islamic boarding school, (2) the reason for the transformation of Islamic boarding school education at PP Darul Dakwah Mojokerto. The results showed that, (1) the educational transformation model at PP Darul Dakwah Mojokerto, this pesantren adopted a selective integration model. (2) the reason for the transformation of Islamic boarding school education in PP Darul Dakwah Mojokerto. There are two reasons, namely, special causes and general causes. The special reason at PP Darul Dakwah is that the transformation took place against the background of the leadership of a kiai and modernization, as well as encouragement from the guardians of students and alumni. The general cause of the transformation of Islamic boarding school education has five aspects that are common causes, namely: cultural aspects, political aspects, economic aspects, leadership aspects and educational aspects.